A cross-sectional study of cigarette smoking, electronic cigarettes among students of Taras Shevchenko Kyiv National University campus - Shcherbaniuk, Ivan; Gnyloskurenko , Ganna; Yaremchenko, Taras; Molochek, Nataliia (The Ukrainian Scientific Medical Youth Journal, 2024)
in the modern world, the problem of the spread of nicotine use is defined as one of the key challenges of public health. Against the backdrop of a decrease in the prevalence of tobacco smoking in the world, the prevalence of electronic cigarettes is rapidly growing, and this process is especially active among young people. Since the emergence of electronic cigarettes on the market, their potential harmful effect on health have been actively investigated, but their safety in the medium and long term is still not well known. Thus recent studies in this direction indicate that there are reasons for concern. The purpose of the study is to assess the prevalence of electronic cigarette use and smoking among students of Taras Shevchenko National University of Kyiv, aged 17 to 23, who lived on the campus at the time of the study. The research was conducted by an anonymous survey. The results were evaluated after processing 370 questionnaires using "MedStat" and "IBM SPSS Statistics" software. The results of the study indicate a high prevalence of smoking and e-cigarette use among students, with 50% of respondents smoking cigarettes or e-cigarettes, and 14.1% combining these bad habits. In addition, gender differences in smoking prevalence and patterns were observed. Women more often than men tried to cigarettes (43.7% vs. 32.6%, p<0.05 ) and electronic cigarettes (39.9% vs. 37.9%), but did not continue smoking them, men smoked cigarettes daily (64.3%) more often than women (38.9%, p<0.01), most of whom smoked cigarettes periodically (61.1%). It was found that smokers are less aware of the harm from cigarettes and electronic cigarettes, compared to non-smokers (77.1% vs. 90.6%, p<0.01). Positive correlations were established between smoking cigarettes and electronic cigarettes (r=0.634, p<0.01), and between personal opinion about the harm to health of cigarettes and electronic cigarettes (r=0.539, p<0.01). The results of the study can serve as a basis for planning further research on this topic, be useful for the development and implementation of practical actions aimed at informing, regulating and controlling the use of electronic cigarettes among young people.